Effect of Viral Replication and Liver Fibrosis on All-Cause Mortality in Human Immunodeficiency Virus–Hepatitis B Virus–Coinfected Individuals: A Retrospective Analysis of a 15-Year Longitudinal Cohort. (1st July 2021) - Dezanet, Lorenza N C; Kassime, Raisha; Miailhes, Patrick; Lascoux-Combe, Caroline; Chas, Julie; Maylin, Sarah; Gabassi, Audrey; Rougier, Hayette; Delaugerre, Constance; Lacombe, Karine; Boyd, Anders
Abstract: Background: In individuals living with human immunodeficiency virus (HIV) and hepatitis B virus (HBV), widespread tenofovir (TDF)–containing antiretroviral therapy (ART) has led to substantial decreases in HBV-DNA and HIV-RNA detection. However, the links between viral replication, liver fibrosis, and mortality remain unclear. Methods: A total of 300 individuals living with HIV-HBV and undergoing ART were prospectively followed. Virological and clinical data were obtained at baseline and every 6–12 months. We quantified the associations between HBV-DNA, HIV-RNA, and liver fibrosis with risk of all-cause mortality using a joint longitudinal survival model. Viral detection, viral loads, and time-averaged cumulative viral loads of HIV and HBV were modeled as 3 separate exposures. Results: During a median of 10.5 years (interquartile range, 4.0–14.6), the proportion undergoing TDF-containing ART (baseline = 18.7%, end of follow-up = 79.1%) and with undetectable HBV-DNA (baseline = 36.7%, end of follow-up = 94.8%) substantially increased. 42 participants died (incidence rate = 1.30/100 person-years, 95% confidence interval [CI] = .96–1.76). The leading causes of death were non-AIDS/non–liver-related malignancies (28.6%), followed by liver-related (16.7%), AIDS-related (16.7%), and other (16.7%). All-cause mortality was associated with HBV-DNA viral load (adjusted hazards ratio [aHR] per log10 IU/mL = 1.41, 95% CI = 1.04–1.93, P = .03) or time-averaged cumulative HBV-DNA (aHR per log10 copy-years = 1.37, 95% CI = 1.03–1.83, P = .03), but not undetectable HBV-DNA. Advanced liver fibrosis at baseline was also associated with increased mortality rates (aHR = 2.35, 95% CI = 1.16–4.76, P = .02). No significant association between HIV-RNA replication and mortality was observed. Conclusions: Concurrent and historical HBV replication and liver fibrosis are important drivers of all-cause mortality in largely TDF-treated individuals living with HIV-HBV, despite one-fifth of deaths being liver-related. HBV-DNA and liver fibrosis remain important prognostic indicators for this patient population. Abstract : Current and cumulative HBV-DNA levels increased the risk of all-cause mortality in HIV-HBV co-infected individuals. Fibrosis was a major determinant of mortality; however, death was mostly caused by extra-hepatic and non-AIDS related diseases.